Prospective Teachers' Metaphorical Perceptions of Sustainability - Kan, Ayse Ulku; Yel, Esra (Mdpi, 2026)
This research aims to examine how the concept of sustainability is understood through metaphors. The research was conducted in accordance with qualitative research principles. The study group was determined using criterion sampling and consisted of 160 prospective teachers studying at a university who had taken and completed the Sustainable Development and Education course. Research data were collected through forms containing the statement, Sustainability is similar to & mldr; Because & mldr;. The data were analyzed through metaphor analysis within a content analysis framework. In total, 160 valid metaphors related to sustainability were identified and organized into three conceptual categories. The results indicate that prospective teachers primarily perceived sustainability in environmental terms, with comparatively less emphasis placed on economic and social dimensions. In addition, sustainability was frequently interpreted as a responsibility to future generations.
Keywords: sustainability; prospective teacher; metaphor; metaphorical perception; environmental sustainability; social sustainability; economic sustainability